2013
DOI: 10.3917/spub.253.0331
|View full text |Cite
|
Sign up to set email alerts
|

Coopération entre médecins généralistes et pharmaciens : une revue systématique de la littérature

Abstract: Cooperation between pharmacists and general practitioners can contribute to improving the quality of primary care, especially in the areas of cardiometabolic and prescription problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 35 publications
0
6
0
1
Order By: Relevance
“…Hitherto, physicians participating in several of these approaches adopted a substantial degree of pharmacists' recommendations for medication change or deprescribing [13,17,18]. Though impact on clinical outcomes is difficult to detect from existing studies [19], collaborative care approaches revealed positive effects for patient-related, procedural and health-economic outcomes [13,[20][21][22][23]. In a wellobserved prospective cohort study in the UK, delegation to clinical pharmacists reduced GP-time spent on key prescribing activities by 51%, equating to 4.9 h of work per week being released [13].…”
Section: Introductionmentioning
confidence: 99%
“…Hitherto, physicians participating in several of these approaches adopted a substantial degree of pharmacists' recommendations for medication change or deprescribing [13,17,18]. Though impact on clinical outcomes is difficult to detect from existing studies [19], collaborative care approaches revealed positive effects for patient-related, procedural and health-economic outcomes [13,[20][21][22][23]. In a wellobserved prospective cohort study in the UK, delegation to clinical pharmacists reduced GP-time spent on key prescribing activities by 51%, equating to 4.9 h of work per week being released [13].…”
Section: Introductionmentioning
confidence: 99%
“…This is striking since numerous studies from various settings provide evidence for the positive effect of community pharmacists on medication management, patient counselling, health education, and improved care resulting in better clinical outcomes [46]. A recent Cochrane Review shows that pharmacist interventions are particularly beneficial for reducing systolic blood pressure, improving HbA1C and blood glucose level, and for the management of asthma [4].…”
Section: Introductionmentioning
confidence: 99%
“…Integration of the eGFR in the prescriptions appeared to them as a supplementary tool for improving this collaboration. A systematic review underlined the fact that the collaboration between general practitioners and pharmacists globally improved the management of the patients, without focalising on patients with CKD (Michot et al ., 2013). In France, a recent decree has recognised these new roles for primary care pharmacists, including extended medical reviews (Arrêté du 9 mars 2018 portant approbation de l’avenant 12 à la convention nationale du 4 mai 2012, organisant les rapports entre les pharmaciens titulaires d’officine et l’assurance maladie, 2018).…”
Section: Discussionmentioning
confidence: 99%